A real story of bioethanol from biomass : Malaysia perspective - H'ng, Paik San; Chin, Kit Ling (InTech, 2013)
Rising fossil fuel prices associated with growing demand for energy, and environment concerns are the key factors driving strong interest in renewable energy sources, particular in biofuel. Biofuel refers to any type of fuel whose energy is derived from plant materials. Biofuel which includes solid biomass, liquid fuels and various biogases is among the most rapidly growing renewable energy technologies in recently. Biofuels are commonly divided into two groups based on the technology maturity which using the terms “conventional” and “advanced” for classification. Conventional biofuel technologies include well-established processes that are already producing biofuels on a commercial scale. These biofuels, commonly referred to as first-generation, include sugar- and starch-based ethanol, oil-crop based biodiesel and straight vegetable oil, as well as biogas derived through anaerobic digestion. First generation biofuel processes are useful but limited in most cases: there is a threshold above which they cannot produce enough biofuel without threatening food supplies and biodiversity. Whereas, advanced biofuel technologies are extensions from conventional technologies which some are still in the research and development (R&D), pilot or demonstration phase and they are commonly referred to as second- or third-generation. This category includes hydrotreated vegetable oil (HVO), which is based on animal fat and plant oil, as well as bioethanol based on lignocellulosic biomass, such as cellulosic-ethanol. Although there are wide varieties of advanced biofuels conversion technologies exists today, but they are not commercially available yet. Nevertheless, the most commercializable technology and most used biofuel on the global market is bioethanol.